Transformation of Social Interaction of Generation Z in the Era of Artificial Intelligence: An Analysis of Changes in Digital Communication Patterns - Ana Lestari; Renita Fitriani (Jurnal Indonesia Sosial Teknologi, 2026)
The development of digital technology and the emergence of Artificial Intelligence (AI) have brought significant changes in people's communication patterns, especially in Generation Z known as the digital native generation. The integration of AI in various communication platforms such as social media, chatbots, and recommendation systems is influencing the way this generation interacts, obtains information, and builds social relationships in the digital space. These changes create new dynamics in social interaction that need to be studied more deeply from a social and technological perspective. This study aims to analyze the transformation of Generation Z's social interaction in the Artificial Intelligence era and identify changes in digital communication patterns that arise due to the use of AI-based technology in daily life. This study uses a qualitative approach with literature study methods and descriptive analysis. Data is obtained from various scientific sources such as journal articles, books, and research reports that are relevant to the topics of social interaction, digital communication, and the development of Artificial Intelligence. The data was then analyzed thematically to identify patterns of change in interaction and communication in Generation Z. The results of the study show that the presence of Artificial Intelligence has changed the communication patterns of Generation Z to be faster, technology-based, and tend to take place in the digital space. AI is also influencing the way this generation accesses information, expresses itself, and builds social relationships. In addition to providing ease and efficiency of communication, the use of AI also raises challenges such as technology dependence, a decrease in the quality of face-to-face interactions, and the potential for the spread of inaccurate information in the digital space.